Business cycle sensitivity of Statutory Health Insurance: evidence from the Czech Republic - Landovská, Petra (Health economics review, 2024)
BACKGROUND: The Statutory Health Insurance scheme is one of two main schemes of health care system financing in Europe. This scheme mainly relies on wage-based contributions from employers and employees and is thus prone to business cycle fluctuations. This turned out to be a problem especially after the 2008 crisis. We estimate the magnitude of the effect of the business cycle on health insurance funds' revenues in the Czech Republic where the health care system financing is based on the Statutory Health Insurance scheme. The relationship between the business cycle and healthcare system's revenues has not been quantified to this date. METHODS: We use static and lagged regression models to estimate the impact of business cycle on health care system's revenues. The business cycle is proxied by eight different indicators (nominal GDP, unemployment, industrial production, recession index, business cycle index, GDP gap, consumer price index and consumer expenditure). Using quarterly data from 2000-2017, we examine the effect of business cycle on total revenues and its two main components: the employer-employee contributions and state contributions. RESULTS: Health insurance funds' revenues display significant pro-cyclicality, which is mainly driven by employer-employee contributions. Out of all eight business cycle indicators, nominal GDP has the largest effect. In particular, the model estimates that if quarter-over-quarter GDP increases by 1%, then quarter-over-quarter healthcare system's revenues increase by 0.7% and quarter-over-quarter employer-employee contributions increase by 1.1%. The lagged effect of business cycle on healthcare system's revenues is smaller in magnitude. State contributions on behalf of economically inactive people do not display a significant relationship with business cycle in the static nor lagged model. The effect is consistent across different business cycle indicators, although the magnitudes of the effect vary. CONCLUSION: The results show large pro-cyclicality in healthcare system's revenues in Statutory Health Insurance schemes. Counter-cyclical mechanisms are needed to offset this loss of revenues during economic downturns to ensure sufficient resources in healthcare.
Keywords: Health system financing; Statutory Health Insurance; Czech Republic; Business cycle